Short-term differences in cardiac function following controlled exposure to cookstove air pollution: The subclinical tests on volunteers exposed to smoke (STOVES) study. (January 2021) - Cole-Hunter, Tom; Dhingra, Radhika; Fedak, Kristen M.; Good, Nicholas; L'Orange, Christian; Luckasen, Gary; Mehaffy, John; Walker, Ethan; Wilson, Ander; Balmes, John; Brook, Robert D.; Clark, Maggie L.; et al.
Highlights: Limited evidence links household air pollution to cardiac function. We evaluated impact of 2-h exposures to 5 cookstoves plus 1 control among 48 healthy adults. Target fine particulate matter concentrations for controlled exposures were 0, 10, 35, 100, 250, 500 µg/m 3. . Short term cardiac function was different after exposure to several cookstoves compared to control. C ookstoves with lower PM2.5 emissions may still be able to adversely affect cardiac function. Abstract: Background: Exposure to household air pollution from solid fuel combustion for cooking and heating is an important risk factor for premature death and disability worldwide. Current evidence supports an association of ambient air pollution with cardiovascular disease but is limited for household air pollution and for cardiac function. Controlled exposure studies can complement evidence provided by field studies. Objectives: To investigate effects of short-term, controlled exposures to emissions from five cookstoves on measures of cardiac function. Methods: Forty-eight healthy adults (46% female; 20–36 years) participated in six, 2-h exposures ('treatments'), including emissions from five cookstoves and a filtered-air control. Target fine particulate matter (PM2.5 ) exposure-concentrations per treatment were: control, 0 µg/m 3 ; liquefied petroleum gas, 10 µg/m 3 ; gasifier, 35 µg/m 3 ; fan rocket, 100 µg/m 3 ; rocket elbow, 250 µg/m 3 ; and three stone fire, 500 µg/m 3 . Participants were treated in a set (pre-randomized) sequence as groups of 4 to minimize order bias and time-varying confounders. Heart rate variability (HRV) and cardiac repolarization metrics were calculated as 5-min means immediately and at 3 h following treatment, for analysis in linear mixed-effects models comparing cookstove to control. Results: Short-term differences in SDNN (standard deviation of duration of all NN intervals) and VLF (very-low frequency power) existed for several cookstoves compared to control. While all cookstoves compared to control followed a similar trend for SDNN, the greatest effect was seen immediately following three stone fire (β = −0.13 ms %; 95% confidence interval = −0.22, −0.03%), which reversed in direction at 3 h (0.03%; −0.06, 0.13%). VLF results were similar in direction and timing to SDNN; however, other HRV or cardiac repolarization results were not similar to those for SDNN. Discussion: We observed some evidence of short-term, effects on HRV immediately following cookstove treatments compared to control. Our results suggest that cookstoves with lower PM2.5 emissions are potentially capable of affecting cardiac function, similar to stoves emitting higher PM2.5 emissions.